Chemically Diverse Secondary Metabolites from Davidia involucrata (Dove Tree) - Li-Yan Song; Ran Lin; Zu-Jian Wu; Ming-An Ouyang (Journal of Chemistry)
Dove tree, Davidia involucrata Baill. which is endemic in western China, is not only one of the best known relict species of the tertiary, but also a famous ornamental plant with dove-shaped flowers. A diverse array of secondary metabolites have been isolated and identified from Davidia involucrata. The 58 structures of the secondary metabolites were presented and classified as triterpenoids, tannins, phenolic compounds, lignans, flavonoids, alkaloids, and sterol. In addition, the biosynthetic route of some triterpenoids was proposed. Moreover, the advances in the discovery of unprecedented compounds and uncovering of notable bioactivities were highlighted in this review.